2014
DOI: 10.1172/jci75801
|View full text |Cite
|
Sign up to set email alerts
|

Stargazing microRNA maps a new miR-21 star for cardiac hypertrophy

Abstract: Left ventricular hypertrophy and microRNAsLeft ventricular hypertrophy (LVH) can be elicited by several clinical conditions, including systemic hypertension, cardiac valve disease, and myocardial infarction, that increase cardiac workload. This adaptation is one facet of cardiac remodeling and subsequent heart failure (HF), which is a major cause of death in Western countries (1). In 1970, the Framingham Heart Study revealed that the presence of LVH alone is associated with increased mortality (1). Moreover, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…it mediates cell-to-cell communications between fibroblasts and cardiomyocytes. 33 To this regard, in the present study, CVS levels of miR-21-3p were significantly correlated with multiple parameters of left ventricular function, such as LVEF, end-diastolic and end-systolic diameters. Also in line with our findings, lower circulating levels of miR-126 had been reported in HF patients, where its levels were correlated with age, left ventricular function, NT-proBNP levels, and left atrial volume.…”
Section: Discussionsupporting
confidence: 47%
“…it mediates cell-to-cell communications between fibroblasts and cardiomyocytes. 33 To this regard, in the present study, CVS levels of miR-21-3p were significantly correlated with multiple parameters of left ventricular function, such as LVEF, end-diastolic and end-systolic diameters. Also in line with our findings, lower circulating levels of miR-126 had been reported in HF patients, where its levels were correlated with age, left ventricular function, NT-proBNP levels, and left atrial volume.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, the ability of exosomes to transfer lipid, RNA, and proteins raises very exciting possibilities for future therapeutic uses. For example, based on the regulatory effects of miR on therapeutic proteins [132, 133], we could engineer host cells to overexpress a specific miR that is capable to be delivered via exosomes. These engineered cells can be either encapsulated to provide sustained local delivery or utilized as “factory” to produce therapeutic exosomes.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…It has been shown that miRNAs are aberrantly expressed in the cardiovascular system under some pathological conditions, including myocardial infarction (19,45), heart failure (6,77), cardiac hypertrophy (36,44), and proliferative thickening of the vessel known as restenosis (15,55).…”
mentioning
confidence: 99%